The Concept of Civil Society and Its Significance on Development Practice - Aswin Ariyanto Azis (Jurnal Transformasi Global, 2016)
The increasing role of civil society in development has challenged the very idea of mainstream development in which state as central actor and infrastructure development is the primary focus. The people-centred development encouraged by civil society and NGO’s has contributed to bring the development back to the people, but in doing so, NGO’s may be perceived as the challenger of the state rather than the coplimentary partner of the state.